Implementation of Murabahah Contract in Pension Financing at BPRS HIK Parahyangan Indramayu Branch - Esha Safitri; Didik Himmawan (Aimmah: Social Sciences Journal, 2025)
Islamic banks are one of the financial institutions that mediate the liquidity needs of the community through various products and services they have. The products owned by Islamic banks are increasingly developing and competing, one of which is a pension financing product which is a consumer financing that is only given to retirees. Murabahah contract is one of the widely used sharia financing instruments, where the Bank buys goods and sells them to customers with an agreed profit margin. Pension financing is one of the financing that has a small risk. The development of Pension Financing customers at BPRS HIK Parahyangan Indramayu Branch has fluctuated. The formulation of the problem in this study is how the application of the murabahah contract in pension financing at BPRS HIK Parahyangan. The purpose of this study is to find out about the application of the murabahah contract in pension financing at BPRS HIK Parahyangan Indramayu Branch. This research is a field research using a qualitative descriptive method. Where the data sources are primary and secondary obtained through interviews, observations and documentation.  Data processing begins with correcting the data, followed by rearranging the data and analyzing the existing data to find results (conclusions) as answers to the problem formulation.